Pendekatan Play Therapy Sebagai Upaya Trauma Healing Pada Anak Terdampak Banjir Pidie Jaya - Adela Wardiansyah, Jumi (Prodi Bimbingan dan Konseling Islam Fakultas Dawah dan Komunikasi UIN Ar-Raniry, 2026)
Flood disasters in Pidie Jaya caused psychological impacts on children, such as fear, anxiety, and difficulties in social interaction after the disaster. This study aimed to describe the implementation of play therapy as a form of trauma healing and to illustrate the emotional and social responses of children during the activities. The study employed a qualitative exploratory approach with data collection techniques through observation, interviews, and documentation. Play therapy activities were carried out through various forms of play, such as singing, drawing, coloring, storytelling, and group games adjusted to the children’s psychological conditions. The results showed that during the activities, children began to demonstrate behavioral changes such as becoming more active in play, more confident in interacting with others, calmer, and better able to express their emotions. In addition, interviews with parents indicated that the children gradually returned to their normal daily activities and no longer showed excessive fear after participating in the play therapy sessions. Therefore, play therapy can serve as a relevant psychosocial approach in supporting the psychological recovery process of children affected by flood disasters. Keywords: play therapy, trauma healing, children, flood disaster, psychosocial